Honduras : Staff Report for the 2005 Article IV Consultation, Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Modification and Waiver of Performance Criteria, and Financing Assurances Review; and Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document. (IMF Staff Country Reports; Country Report, 2006)
This paper examines Honduras's 2005 Article IV Consultation and Second Review Under the Poverty Reduction and Growth Facility. In the period 1960-2000, output growth in Honduras ranked among the lowest in the region. During the 1990s, when growth recovered in the rest of Central America, in Honduras it only kept pace with population growth. The authorities embarked on an economic reform program that focuses on ensuring macroeconomic stability and strengthening growth prospects through the development of human capital and basic infrastructure.